Pengaruh Perlakuan Uap Air Panas dengan Sistem Pemanasan Terbuka terhadap Kesehatan dan Viabilitas Benih Jagung - Singgih Kurniawan; Ani Widiastuti; Y. M. S. Maryudani (Universitas Gadjah Mada, 2008)
The existence of seed-borne fungi could degrade the seed quality in its viability and may cause disease after planting. The aim of this research was to know the hot vapor treatment effectiveness in controlling that fungal disease and its influence to the viability of corn seed. The treatment effectiveness was measured based on the reduction of the fungal growth and sporulation on Potato DextroseAgar (PDA), the fungal infection on seed, and not reduced the seed viability significantly after treatment. Hot vapor treatment was done in 50°C, 60°C, and 70°C temperature for 20 minutes and a control. The temperature treatments cover 5 minutes of antecedent treatment in the form of appliance warm-up until the target temperature obtained, 10 minutes in the treatment drum and 5 minutes for resting time while the faucet is being shut down but the exhaust fan remain to be opened. Result of the research show that in vitro test of hot water vapor on 60oC and 70oC killed Aspergillus flavus, A. niger, Fusarium sp., and Penicillium sp. isolates. Both of the temperatures reduced the corn seed viability significantly. Infection of A. flavus still dominant in corn seed after treated on the three temperatures.The hot vapor treatment with 50oC is good for seed treatment of 408.9 g corn seed although the seed had been stored for about 9 months.